Application Of Al-Qur'an Murotal Therapy to Reduce Pain Intensity in Post-Laparotomy Patients - Andry Sartika; Mardani Salman; Iis Suryani (JOSING: Journal of Nursing and Health, 2026)
This study aim was to explain Askeps with the application of Al-Qur'an murotal therapy to reduce pain intensity in post-laparotomy patients in the Azzahra Room’s Hospital PKU Muhammadiyah Gamping Jogyakarta. This research design uses case study method. The sampling method used is purposive sampling. The sample taken is one respondent, namely Mrs. Y, a post-laparotomy patient in the Azzahra Room’s Hospital PKU Muhammadiyah Gamping Jogyakarta in August 2022. The research data were taken as primary data by conducting direct assessments of the assisted patients. Existing data were analyzed using explanatory and time series analysis. The conclusion, showed that the application of Al-Qur'an murotal therapy can reduce pain intensity in post-laparotomy patients.    Keywords : Al-Qur'an Murotal Therapy, Pain Intensity and Post-Patient        Laparotomy Surgery